The conserved transcription factors, MYB115 and MYB118, control expression of the newly evolved benzoyloxy glucosinolate pathway in Arabidopsis thaliana - Zhang, Yuanyuan; Li, Baohua; Huai, Dongxin; Zhou, Yongming; Kliebenstein, Daniel J. (Frontiers in Plant Science, 2015)
The evolution of plant metabolic diversity is largely driven by gene duplication and ensuing sub-functionalization and/or neo-functionalization to generate new enzymatic activities. However, it is not clear whether the transcription factors (TFs) regulating these new enzyme encoding genes were required to co-evolve with these genes in a similar fashion or if these new genes can be captured by existing conserved TFs to provide the appropriate expression pattern. In this study, we found two conserved TFs, MYB115 and MYB118, co-expressed with the key enzyme encoding genes in the newly evolved benzoyloxy glucosinolate (GLS) pathway. These TFs interacted with the promoters of the GLS biosynthetic genes and negatively influenced their expression. Similarly, the GLS profiles of these two TFs knockouts showed that they influenced the aliphatic GLS accumulation within seed, leaf and flower, while they mainly expressed in seeds. Further studies indicated that they are functionally redundant and epistatically interact to control the transcription of GLS genes. Complementation study confirmed their roles in regulating the aliphatic GLS biosynthesis. These results suggest that the newly evolved enzyme encoding genes for novel metabolites can be regulated by conserved TFs, which helps to improve our model for newly evolved genes regulation.